SYSTEMATIC LITERATURE REVIEWS: SISTEM MERIT DALAM MANAJEMEN SUMBER DAYA MANUSIA SEKTOR PUBLIK - Tri Raharjanto (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
This study aims to answer conceptual and practical questions about how the concept of merit systems in human resource management, and how to design and implement merit systems abroad. The method applied is Systematic Literature Reviews, which is a literature review method that identifies, evaluates, and interprets all findings on a research topic to answer previously determined research questions. It can be concluded that the concept of merit system in human resource management is a system that places employee competency and performance as the main considerations in selection and promotion. Until now, there is no single design of a merit system that is universal, because each country will make adjustments to their respective legal, social andcultural systems. Furthermore, as a relatively new system in Indonesia, the initial dynamics of the implementation of the merit system were still tinged with various technical and political problems at the regional level. Keywords: Human Resource Management; Merit System; Meritocracy